PEMBELAJARAN TRANSFORMATIF BERBASIS LITERASI DAN NUMERASI DI SEKOLAH DASAR - Fitriana, Evi; Khoiri Ridlwan, Muhamad (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2021)
Transformative learning based on literacy and numeracy in elementary schools in thematic lessons from grades 1-6 can be implemented by providing stimulus to students. Literacy and numeracy are important skills that must be possessed by elementary school students to support their abilities in education, reach their potential, and participate in society. This article will review the concept of transformative learning based on literacy and numeracy for elementary school children. The theory of transformative learning and the concept of numeracy literacy are elaborated as the development of learning concepts because transformative learning does not only transfer knowledge but also makes changes, especially understanding literacy and numeracy.